Purpureocillium lilacinum as an Agent of Nematode Control and Plant Growth-Promoting Fungi - Rigobelo, Everlon Cid [UNESP]; Nicodemo, Daniel [UNESP]; Babalola, Olubukola Oluranti; Desoignies, Nicolas (MDPI, 2024)
Plants support numerous microorganisms within their tissues and the rhizosphere, and these microorganisms, known as the microbiota, can influence plant growth and health. Up to 40% of a plant’s photosynthetic metabolism may be invested in the rhizosphere. The microbiota is considered an extra genome that can be modulated to meet plant needs. Researchers have identified a set of genes from these microorganisms, known as the microbiome, which can be manipulated to enhance plant growth and health, improve nutrient absorption, reduce the need for chemical fertilizers, increase resistance to pathogens and pests, and increase stress tolerance. In particular, fungi exhibit large genetic and metabolic diversity and are often used to promote plant growth. For example, the fungus Purpureocillium lilacinum has been employed primarily as a biocontrol agent to manage nematodes, but some studies have suggested that it may also promote plant growth by increasing the efficiency of the plant in absorbing nutrients from the soil and providing phytohormones to plants. Therefore, the current review aims to summarize the existing literature on the use of this fungus in agriculture as nematodes control, and discuss its potential as a plant growth-promoter.
Keywords: phosphorous solubilizing; tobacco virus; tomatoes; yield increasing